The era of clinical application of gene diagnosis in cardiovascular diseases is coming. Issue 4 (December 2019) - Zou, Yu-Bao; Hui, Ru-Tai; Song, Lei
Abstract: Gene diagnosis refers to the use of genetic testing in the diagnosis of inheritable conditions, which has gradually been applied in clinical practice with the completion of the gene sequencing efforts of the Human Genome Project and the advancement of gene detection technology. In the specialty field of cardiology, monogenic cardiovascular diseases are defined as monogenic inherited diseases with cardiovascular damage as the only phenotype, or accompanied by cardiovascular damage. Although the incidence of such diseases is relatively low, in the country of China with its vast population of 1.33 billion, the sheer volume of patients with monogenic cardiovascular diseases is alarming. With early onset, severe symptoms, and poor prognosis, delays in diagnosis and treatment of monogenic cardiovascular diseases often have serious consequences. Gene testing is perfectly suited for early diagnosis of monogenic cardiovascular diseases, especially for "pre-symptomatic" diagnosis. In this article, we generally review the characteristics of common monogenic cardiovascular diseases, summarize the progress of the standardized application of gene testing technology in clinical practice, describe the applicable population and condition of genetic testing for different monogenic cardiovascular diseases, analyze the practicality of genetic diagnosis of these inheritable conditions, and provide guidance on identifying suitable candidates for gene diagnosis. In conclusion, gene diagnosis provides new insights into the way physicians diagnose diseases, and is well-positioned to guide clinical decision making and treatment, especially in cardiology.